Openness reexamined: teachers' practices with open educational resources in online language teaching. Issue 2 (2nd April 2020) - Pulker, Hélène; Kukulska-Hulme, Agnes
ABSTRACT: Open educational practices (OEP) as a research field is relatively new. One aspect that has received limited attention is the impact of using open educational resources (OER) on the development of OEP. This article, based on a doctoral study (Pulker, 2019), considers teachers' activities when reusing and adapting OER, with a view to providing evidence of reuse and understanding whether these activities influence teaching practices. A qualitative study following a constructivist grounded theory methodology was undertaken with 17 part-time online language teachers via semi-structured interviews. The article presents the five-step model of reuse that emerged from the data analysis. We suggest that OER reuse has a positive impact, even though teachers' practices might not be open as defined up until now. A graphic representation depicts the process that teachers engage with when using and adapting OER. The research brings new understanding of teachers' experiences of reuse, showing that the principal motivation is enhancing students' learning.